Hubungan Antara Kontrol Diri Dengan Perilaku Agresif Dalam Berkendara Pada Komunitas Motor Di Kota Surakarta - Cahyo Sulistyo, Firman, Achmad Dwityanto, S.Psi, M.Si (2017)
ABSTRACT THE RELATIONSHIP BETWEEN SELF-CONTROL WITH THE BEHAVIOR AGGRESSIVE IN DRIVING ON A COMMUNITY MOTORCYCLE ON SURAKARTA CITY Firman Cahyo Sulistyo Firmancahyo14@gmail.com Achmad Dwiyanto, S.Psi, M.si Faculty of Psychology, Muhammadiyah University of Surakarta Aggressive behavior rider happening on roads that is honking when at a red light , nudging other motorists with intention injure , breaking a red light , breaking markings and others .When it appeared aggressive behavior , each individual having a mechanism that can help , set and directing behavior that is self-control .Self-control in need when penendara was on the road .It is meant to the rider can drive calmly and has not problems when berkendara.tujuan from the study are ( 1 ) to know the relationship between self-control with the behavior aggressive in driving in the rider , ( 2 ) order to know the level self-control in motorists , ( 3 ) order to know the level behavior aggressive in motorists, ( 4 ) to know contributions effective control variables himself against aggressive behavior. Hypothesis advanced by which is there are negative relations between self-control with the behavior aggressive in driving.Technique the sample used in this research was using a technique purposive sampling, with the subject of 85.Using a technique the sample collection purposive sampling. A measuring instrument used to uncover variabel-variabel research is kind of the gauge 2 , namely: ( 1 ) scale self control and ( 2 ) scale aggressive behavior .Analysis techniques data using the correlation product moment .Analysis of data to research it uses spss 15.0 , obtained the value of a correlation coefficient of -0,579 with significance ( p ) = 0,000; (p≤0,01 ) which means there is a negative highly significant between control behaviors aggressive in driving. Empirical mean variable self control of 76,94 with mean hypothetic 60 . It shows that empirical mean > hypothetic mean that illustrates that the average motorists have self control high .The empirical mean variable aggressive behavior of 44,41 with mean hypothetic of 57,5 . It shows that empirical mean > hypothetic mean that illustrates that motorists have aggressive behavior low .The role of control of aggressive behavior of 33,5 % which means there are still 66,5 % affecting aggressive behavior .Such factors include: mannerisms riders , the age and sex. Keywords : Self Control , Aggressive Behavior